TUBERKULOSIS TRAKTUS URINARIUS - Lalu Shaktisila Fatrahady (Faculty of Medicine Universitas Mataram, 2021)
Tuberculosis (TB) is an infectious disease caused by the bacteria MTB (Mycobacterium Tuberculosis). TB can affect all organs, especially the lungs as primary infection site, and outside the lungs (extra-pulmonary TB) such as the skin, lymph nodes, bones, urinary tract (kidneys, ureters, and bladder), testes, and the membranes of the brain. TB is transmitted through infectious droplets inhaled by healthy people. Renal tuberculosis usually originates from hematogenous spread from the lungs, although sometimes it can originate from the gastrointestinal tract or bone. Tuberculosis of the ureters and bladder occurs secondary to the flow of urine from the kidneys. TB can also occur in the urethra, but it is rare. Clinical manifestations of urinary tract TB can be fever, hematuria, low back pain or pyuria. Complications of urinary tract TB can occur urinary tract obstruction due to strictures, urosepsis, and kidney failure, both acute and chronic. Treatment for urinary tract tuberculosis is same as for pulmonary tuberculosis. Surgery treatment is required if there is obstruction of the urinary tract.